Composition Elements of the Traditional Joget Utan Dance in Bunjung Village Siak Regency - Yahyar Erawati; Syahrul Syah Sinaga (Universitas Negeri Medan, 2023)
This research aims to examine the elements of dance composition in the Joget Utan traditional dance in Bunsur Village, Sungai Apit District, Siak Regency. The Joget Utan dance is rich in cultural values and is a legacy from previous generations. The traditional Joget Utan dance is an integral part of the life of the local community. However, there has been no research that has studied in depth the elements of this dance composition. Therefore, this research aims to fill this gap and provide a deeper understanding of the elements involved in the Joget Utan dance. The research method uses a qualitative approach with data collection methods through direct observation of dance performances, interviews with dancers and local community leaders, as well as literature study to obtain information on the Joget Utan dance. The collected data will be analyzed descriptively to describe the elements of dance composition. By following this stage, it is hoped that we can provide better insight into the richness of Joget Utan dance culture and contribute to efforts to preserve and develop this traditional dance art